1979
DOI: 10.1029/jc084ic09p05707
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the lipid compositions of marine aerosols, the sea surface microlayer, and subsurface water

Abstract: Aerosols, surface microlayer, and subsurface water samples have been collected during the 'Midlante' cruise of the R/V Jean Charcot (May 1974) in the northeastern tropical Atlantic, taking all possible precautions against shipboard contamination. The concentrations of n alkanes, total hydrocarbons, and fatty acids (C•2 to C32 were obtained by gas-liquid chromatography in these aerosol samples as well as for the dissolved and particulate fractions of the microlayer and subsurface waters. The aqueous phase fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(108 citation statements)
references
References 26 publications
2
105
1
Order By: Relevance
“…Since there are no important sources for elemental carbon in the Southern Ocean, water-insoluble organic compounds might have been more enriched in the aerosols in this region. Unsaturated fatty acids are a likely source of aerosol TC since they are major lipid components in the marine algae and are enriched in the micro-layers of sea surfaces (Marty et al, 1979). The levels of DCAs-C/TC over the western Pacific in this work are significantly higher than those (1.3 to 4.6%) observed in Tokyo (Sempéré and Kawamura, 1994), demonstrating that photochemical production of DCAs during the long-range atmospheric transport may be important in the Pacific.…”
Section: Resultscontrasting
confidence: 52%
“…Since there are no important sources for elemental carbon in the Southern Ocean, water-insoluble organic compounds might have been more enriched in the aerosols in this region. Unsaturated fatty acids are a likely source of aerosol TC since they are major lipid components in the marine algae and are enriched in the micro-layers of sea surfaces (Marty et al, 1979). The levels of DCAs-C/TC over the western Pacific in this work are significantly higher than those (1.3 to 4.6%) observed in Tokyo (Sempéré and Kawamura, 1994), demonstrating that photochemical production of DCAs during the long-range atmospheric transport may be important in the Pacific.…”
Section: Resultscontrasting
confidence: 52%
“…The surface potentials of the compounds are compared (Table 1) by measuring AV, at the point where the film has initially formed a close-packed monolayer but is not yet under further compression (henceforth referred to as a noncompressed, close-packed monolayer), taken at the intersection of the tangent to the yf vs. A compression curve with the A-axis (Langmuir 1917). Stearic, myristic, palinitic, palmitoleic, and oleic acids are the principal fatty acids found in sea surface film hydrolysates (Garrett 1964;Duce et al 1972;Larsson et al 1974;Daumas et al 1976;Kattnel and Brockmann 1978;Marty et al 1979) and probably occur in natural films primarily as components of triglycerides, wax esters, phosphol ipids, and as free fatty acids. The AV, values for stearic acid at pH 3.0 and 8.2 are +380 and -5 (Table 1); Fig.…”
Section: Muteandismentioning
confidence: 99%
“…7,8 Phospholipids and fatty acids (mainly C 12À18 ) are common products of biomembrane disintegration. 9,10 Previous work has indicated that fatty acid lipids in sea salt particles can be enhanced by factors of (5-9) Â 10 4 compared to ocean surface water. 10 In addition to the material from biomembranes, bacteria can also be enriched on the particle surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Previous work has indicated that fatty acid lipids in sea salt particles can be enhanced by factors of (5-9) Â 10 4 compared to ocean surface water. 10 In addition to the material from biomembranes, bacteria can also be enriched on the particle surfaces. 11,12 An organic coating on sea salt particles is expected to modify the chemical and physical properties of the particles including their radiative properties.…”
Section: Introductionmentioning
confidence: 99%